Fast, "robust", and approximately correct: Estimating mixed demand systems - Bernard Salanié; Frank A. Wolak (Centre for Microdata Methods and Practice (cemmap), 2018)
Many econometric models used in applied work integrate over unobserved heterogeneity. We show that a class of these models that includes many random coefficients demand systems can be approximated by a "small-o" expansion that yields a straightforward 2SLS estimator. We study in detail the models of market shares popular in empirical IO ("macro BLP"). Our estimator is only approximately correct, but it performs very well in practice. It is extremely fast and easy to implement, and it accommodates to misspecifications in the higher moments of the distribution of the random coefficients. At the very least, it provides excellent starting values for more commonly used estimators of these models.
Keywords: 330